2020
DOI: 10.2495/eq-v5-n3-223-233
|View full text |Cite
|
Sign up to set email alerts
|

A CPFD model to investigate the influence of feeding positions in a gasification reactor

Abstract: The efficiency of a gasification process is directly related to the rate of biomass conversion into product gas. The rate of fuel conversion depends on the interaction of fuel with the bed material, the gasifying agent, and the residence time of fuel particles. The interactions and the residence time depend on the fuel feeding positions along the height of the reactor. Thus, the fuel feeding position in a gasification reactor is an important parameter that influences the efficiency of the gasification process;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Wang et al [314] performed coal gasification in a CFB in order to compare on-bed feeding and feeding from the loop seal (the feed was injected into the bed), and reported that coal feeding by loop seal was an effective way to improve the gasification performance because the residence time was prolonged by making the coal to circulate through the whole furnace. The same conclusion was drawn by [328] based on a CPFD model for a fluidized bed reactor.…”
Section: Location Of the Feeding Pointsupporting
confidence: 75%
“…Wang et al [314] performed coal gasification in a CFB in order to compare on-bed feeding and feeding from the loop seal (the feed was injected into the bed), and reported that coal feeding by loop seal was an effective way to improve the gasification performance because the residence time was prolonged by making the coal to circulate through the whole furnace. The same conclusion was drawn by [328] based on a CPFD model for a fluidized bed reactor.…”
Section: Location Of the Feeding Pointsupporting
confidence: 75%